2016
DOI: 10.37761/rsqp.v82i3.58
|View full text |Cite
|
Sign up to set email alerts
|

EVALUACIÓN DEL CONTENIDO DE POLIFENOLES TOTALES Y LA CAPACIDAD ANTIOXIDANTE DE LOS EXTRACTOS ETANÓLICOS DE LOS FRUTOS DE AGUAYMANTO (Physalis peruviana L.) DE DIFERENTES LUGARES DEL PERÚ

Abstract: El aguaymanto es una especie nativa de la serranía peruana, que posee un diminuto fruto que discrepa con su grandeza nutricional y terapéutica. La presente investigación tuvo como objetivos valorar y comparar el contenido de polifenoles totales por el método de Folin- Ciocalteu y la capacidad antioxidante de los frutos de Physalis peruviana L., provenientes de Huánuco, Junín, Ancash y Cajamarca, por el método del DPPH (1,1-difenil-2-picrilhidrazilo). El fruto procedente de Huánuco presentó mayor contenido de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…It is common to find a correlation between the content of and AC; however, in Ataulfo mango it has already been reported that there is no total correlation between both characteristics [5,7]. The nature and proportion of each of the phenolic compounds is also decisive in the correlation or not between TPC and AC, since certain types of TPC (chlorogenic acid, gallic acid, vinylic acid and others) exert greater AC and these could be found in different concentration in the fruits of the different municipalities as it has been reported occurs in mango fruits grown in China, as well as various varieties of fruits [17,22,23].…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…It is common to find a correlation between the content of and AC; however, in Ataulfo mango it has already been reported that there is no total correlation between both characteristics [5,7]. The nature and proportion of each of the phenolic compounds is also decisive in the correlation or not between TPC and AC, since certain types of TPC (chlorogenic acid, gallic acid, vinylic acid and others) exert greater AC and these could be found in different concentration in the fruits of the different municipalities as it has been reported occurs in mango fruits grown in China, as well as various varieties of fruits [17,22,23].…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…Recently, studies on the genetic characterization and molecular cytogenetics of fruits grown in Peru have been conducted [9,38] to understand the biological and genetic diversity of this species. However, there are only a few studies that refer to the chemical composition and nutritional and antioxidant capacity of P. peruviana cultivated in Peru [20,25]. This limited knowledge affects the production and export chain, both of the fruit and the processed foods based on this resource.…”
Section: Introductionmentioning
confidence: 99%
“…Se disolvió en 1 L de agua destilada (31,32). La solución fue esterilizada mediante autoclave (45 minutos a 121°C) y se almacenó hasta el momento de su uso (32).…”
Section: Elaboración Del Cultivo En Medio Luria Bertaniunclassified